Of port infrastructures and riverine communities: navigating the variegated urbanization processes along the Sarawak River - Azmah, Arzmi (National University of Singapore and John Wiley & Sons Australia, Ltd., 2025)
Rivers have long been vital arteries for urban development, shaping the spatial and social fabric of cities. This study examines the Sarawak River in Kuching, focusing on how zoning activities and the relocation of port facilities have reshaped the city’s urban landscape. By analysing the impact of port infrastructure projects and shipping regulations, this research explores the urban transformations that have taken place over the past century. Using a combination of qualitative and empirical methods, the paper sheds light on the experiences of riverine communities, the gentrification of the waterfront and the emergence of industrial zones. It shows how the instrumentalization of the river for economic purposes has led to a fragmented urban fabric characterized by industrial zones and logistics hubs. This process has often marginalized riverine communities and contributed to the deterioration of the ecosystem and dwindling fish production. Using the framework of planetary urbanization, this work evaluates the impact of river zoning on the spatial configuration of Kuching, thereby highlighting the challenges faced by postcolonial cities on efforts in balancing rapid urbanization with social and environmental sustainability.